Uric acid metabolic disorders in children with acute infectious diarrhea - S. V. Khaliullina (Rossijskij Vestnik Perinatologii i Pediatrii, 2016)
Objective: to estimate the prevalence and clinical features of acute intestinal infections running with hyperuricemia in children. Patients and methods. A cross-sectional study was conducted in 203 children with acute enteric infections. Group 1 (a study group) included 22 children whose serum uric acid level was above 416 μmol/l and Group 2 (a control group) comprised 120 children with normal uric acid level (120—320 μmol/l). Results. Diagnostically significant hyperuricemia was registered in 10,8% of the children. The etiology of acute infectious diarrhea had no significant impact on the registration rate of hyperuricemia. Gastrointestinal tract damage as gastroenterocolitis more than doubled the risk of hyperuricemia (prevalence ratio (PR)=2,7; CI 1,03—7,2). The presence of vomiting increased the probability of detecting hyperuricemia by 1,6 times (PR=1,6; CI 1,1—2,3). Conclusion. Secondary hyperuricemia occurs more frequently in children aged 3 to 7 years. In our study, it was equally often recorded in both viral and bacterial acute enteric infections appearing as gastroenterocolitis with vomiting, dehydration, and acetonemic syndrome.